Soeharto & bangkitnya kapitalisme Indonesia / Richard Robison; Penerjemah, Harsutejo; Penyunting, Sinthawati Soemardi dan Prima H. Patriyawhura - ROBINSON, Richard; HARSUTEJO; SHINTAWATI Soemardi; PRIMA H. Patriyawhura (Komunitas Bambu, 2012)
xxx, 346 hlm. ; 24 cm.